APPROCHE DES CRIS PHILOSOPHIQUES. FORMES DE PENSÉES SINGULIÈRES DANS LES PRATIQUES PHILOSOPHIQUES AVEC LES ENFANTS - FOURNEL, Anda (Studia Universitatis Babeș-Bolyai Philosophia, 2019)
The discursive and reflexive practices falling within Philosophy for children (P4C) program aim to enable children to develop autonomous and authentic thinking by transforming the class into a community of philosophical inquiry. The educational program’s initiators put forward the idea that learning to think cannot exclusively follow a rationality model. Considering Deleuze distinction (1984) between cry of reason and cry of unreason as a starting point, we are interested in cry’s specimens – the concept and the question – as the call’s living forms in philosophical thought, linked to the emotions’ expression. Our investigation explores the folds of children’s thinking, through a qualitative analysis of classroom recordings in primary and middle school, in order to asses children’s ability to provide philosophical cries. If so, one might wonder what do they shout and how do they do it?